Dynamic Changes in Gene Mutational Landscape With Preservation of Core Mutations in Mantle Cell Lymphoma Cells - Zhang, Qian; Wang, Hong Y.; Liu, Xiaobin; Roth, Michael H.; Shestov, Alex A.; Lee, Seung-Cheol; Jain, Kanika; Soderquist, Craig; Xiong, Qun-Bin; Ruella, Marco; Strauser, Honore; Glickson, Jerry D.; et al. (Frontiers in Oncology, 2019)
While the studies identified a number of mutations in mantle cell lymphoma (MCL), the list may still be incomplete and contribution to the pathogenesis remains unclear. We analyzed mutational landscape of four mantle cell lymphoma biopsies obtained in the 8-year period from the same patient with his normal cells serving as control; we also established a cell line from the final stage of the disease. Numerous mutations with high allelic burden have been identified in all four biopsies. While a large subset of mutations was seen only in individual biopsies, the core of 21 mutations persisted throughout the disease. This mutational core is also maintained in the cell line that also displays DNA-methylation and cytokine-secretion profiles of the primary mantle cell lymphoma cells. This cell line is uniquely sensitive to clinically relevant inhibitors of Bruton’s Tyrosine Kinase. The response to Bruton Tyrosine Kinase’s inhibition is enhanced by inhibitors of CDK4/6 and mTOR. Among the mutations seen in the primary and cultured MCL cells, mutations of three genes involved in the control of H3K4 methylation: demethylase KDM5C present already in the early disease, methyltransferase KMT2D and cofactor BCOR, both seen late in the disease, are novel and predicted to be pathogenic. The presence of these mutations was associated with hypermethylation of H3K4. Restoration of KDM5C expression affected the expression of numerous genes involved in cell proliferation, adherence/movement, and invasiveness.